Evaluating Professional Development for Islamic Education Teachers in Palembang, Indonesia - Rahmawati Rahmawati; Mardiah Astuti; Afriantoni Afriantoni; Yuniar Yuniar (Journal of General Education and Humanities, 2026)
This study evaluates the effectiveness of a professional development program for Islamic education teachers organized by the Palembang City Government, Indonesia. Despite the growing number of teacher-training initiatives, empirical evaluations of programs specifically designed for Islamic education teachers remain limited, particularly at the local government level. Therefore, this study aims to examine the program’s effectiveness in improving teachers’ competencies using the Context, Input, Process, and Product (CIPP) evaluation framework. The study employed a sequential explanatory mixed-methods design. Quantitative data were collected through questionnaires from 66 Islamic education teachers, while qualitative data were obtained through interviews, observations, and document analysis. The quantitative results indicate very high levels of agreement across all CIPP components: 94.53% for context evaluation, 95.53% for input, 97.02% for process, and 98.51% for product evaluation. The findings also indicate improvements in teachers’ professional, pedagogical, personality, and social competencies after participating in the program. These results suggest that the program effectively enhances teachers’ instructional capacity and supports improvements in the quality of Islamic education. This study provides empirical evidence on the effectiveness of local government-led professional development programs and contributes to the application of the CIPP evaluation model in Islamic education policy contexts.